Diploid/triploid mixoploidy: A consequence of asymmetric zygotic segregation of parental genomes. Issue 12 (10th October 2018) - Carson, Jason C.; Hoffner, Lori; Conlin, Laura; Parks, W. Tony; Fisher, Rosemary A.; Spinner, Nancy; Yatsenko, Svetlana A.; Bonadio, Jeffrey; Surti, Urvashi
Abstract : Triploidy is the presence of an extra haploid set of chromosomes and can exist in complete or mosaic form. The extra haploid set of chromosomes in triploid cells can be of maternal or paternal origin. Diploid/triploid mixoploidy is a unique form of triploid mosaicism that requires the aberrant segregation of entire parental genomes into distinct blastomere lineages (heterogoneic cell division) at the earliest zygotic divisions. Here we report on eight cases of diploid/triploid mixoploidy from our institution and conduct a comprehensive review of the literature. The parental origin of the extra set of chromosomes was determined in two cases; and, based on phenotypic evidence we propose the parental origin in the other cases. One case with complex mixoploidy appears to have a digynic origin in addition to the involvement of two different sperm. Of our eight cases, only one resulted in the birth of a live healthy child. The other pregnancies ended in miscarriage, elective termination of pregnancy, intrauterine fetal demise or neonatal death. A review of the literature and the results of our cases show that a preponderance of recognized cases of diploid/triploid mixoploidy has a digynic origin.